Pressure wave generation from perturbed premixed flames. (17th May 2016) - Blanchard, Mathieu; Schmid, Peter J.; Sipp, Denis; Schuller, Thierry
Abstract : Numerical simulations and perturbation analysis of a radially imploding laminar premixed flame are used to study the mechanisms responsible for the generation of pressure fluctuations at flame fronts for various Lewis numbers. The relative importance of mechanisms based on unsteady heat release and on vorticity is investigated using an optimization methodology. Particular attention is paid to the influence of non-axisymmetric conditions and local flame curvature. It is shown that vorticity-based noise generation prevails for high-wavenumber, non-axisymmetric disturbances at all curvatures, while heat-release-driven noise generation dominates the axisymmetric and low-wavenumber regimes. These results indicate that short-wavelength vorticity waves actively participate in flame acoustic activity and can surpass acoustic output mechanisms based on heat-release fluctuations in the vicinity of the flame front.